Role of the nurse in preventing or reducing increase intracranial pressure following craniotomy - Abdelmowla, Rasha; Essa, Abdelhakeem; Abdelmaged, Esmat (International Journal of Advanced Nursing Studies, 2017)
Background: Increase intracranial pressure following craniotomy is common and different measures should be taken to prevent or treat it promptly. Aim: Preventing or reducing increase intracranial pressure following craniotomy. Research design: Quasi-experimental. Subjects and methods: All nurses (26) in neurosurgery department at Assiut Neurological, Psychiatric and Neurosurgery University Hospital, in addition to a sample of 124 patients after craniotomy. Control group (62 adult patients before implementing the nursing educational program) and study group (62 adult patients after implementing the nursing educational program). Nurses’ knowledge and practice were assessed before and after implementation of the nursing educational program. Tools: Structured questionnaire to assess nurses` demographic data and knowledge about intracranial pressure, observation checklist for nurses` practice, patients’ assessment sheet, and teaching booklet for nurses about postoperative increase intracranial pressure. Results: Highly significant differences were found as regarding nurses` knowledge and nurses` practice pre and post implementing the nursing educational program. Significant difference was found between study and control groups as regarding increase intracranial pressure following craniotomy. Conclusion: Nursing educational program had a significant effect on preventing or reducing postoperative increase intracranial pressure. Recommendation: Nurses should have continuous education through programs, workshops, seminars and/or training courses to maintain high quality care.